Дьявольские наслаждения: роман / Д. Хантер ; пер. И. Г. Ирская - Хантер Джиллиан (Очарование, 2011)
Экземпляры: ОРФ (2011) / Инвентарный номер: 47448 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: Х 19 / ББК: 84(7Сое)